Alternatif Strategi Pengembangan Desa Rahtawu Sebagai Daya Tarik Wisata di Kabupaten Kudus - Prasetyo Adi Suryo Wibowo; Samsul Ma’rif (Jurnal Wilayah dan Lingkungan, 2014)
Colo Natural Tourism is a one of place a natural tourism which developed in Kudus Region. This place attracts tourists because it has a beautiful natural resources and interesting activities. Based on tourism development, issues that often arise in every tourist attraction are such as limited tourism facilities and infrastructure and the lack of interest of the community to a tourist attraction. Those issues can be solved by providing enough and equitable facilities and infrastructures, increasing promotion of tourism attractions in order to attract visited tourist. Different with Colo Tourism, there is Rahtawu Tourism Village which is less developed. As a tourism object, Rahtawu Tourism Village has potential spot to be developed such as waterfalls and river which are still clear and it has a breathtaking mountain view. Therefore, Rahtawu Tourism Village needed to be developed to increase the interest of tourists as well as Colo Tourism does. This study aims to investigate the alternative of Rahtawu Tourism Village development as a tourist attraction in the Kudus Region which is join with Colo or develop by own resources. The method that used is technically supported by descriptive analysis analytic hierarchy process (AHP) and it is supported by qualitative analysis. The AHP analysis was involving several informants who are the stakeholders of tourism development of Rahtawu Village. The results of this study indicate that informants choose the alternative that Rahtawu should develop by its own (65.16%) and the rest 34.84% choose joined with Colo Tourism. Tourism elements that influence for Rahtawu development are 34.04% for Rahtawu tourist attractions (first priority), 17.02% for transportation, accommodation and promotion (second priority), and the last but not least (last priority) is 14.89% for visitors. Therefore, the first priority of the development is improving the existing tourist attractions by providing tourism facilities and infrastructure.